Sundanese Traditional Tone Sensitivity-Based Audiation Model of Salendro Musical Scale - Latifah, Diah (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2016)
This study is aiming at finding out the audiation model of salendro musical scale and teaching it to the non-Sundanese learners. Treatment done to the learners whose hearing sensitivity has not been familiar with salendro tone during the audiation practice. A method implemented in the study was grounded theory. It was used to explore initial audiation theory from Edwin E. Gordon in Syntax Learning Sequence in Music that was adjusted with learning stages of salendro tone. This study resulted in an audiation model of salendro tone to sharpen hearing sensitivity of non-Sundanese learners who had not been familiar with salendro tone.